UK national guidelines on the management of syphilis 2015. (May 2016) - Kingston, M; French, P; Higgins, S; McQuillan, O; Sukthankar, A; Stott, C; McBrien, B; Tipple, C; Turner, A; Sullivan, AK; Radcliffe, Keith; et al.
These guidelines are an update for 2015 of the 2008 UK guidelines for the management of syphilis. The writing group have piloted the new BASHH guideline methodology, notably using the GRADE system for assessing evidence and making recommendations. We have made significant changes to the recommendations for screening infants born to mothers with positive syphilis serology and to facilitate accurate and timely communication between the teams caring for mother and baby we have developed a birth plan. Procaine penicillin is now an alternative, not preferred treatment, for all stages of syphilis except neurosyphilis, but the length of treatment for this is shortened. Other changes are summarised at the start of the guideline.